Management Leadership and Educational Innovation: The experience of a Northeastern Mexican normal school - González Rivera, Petra Eufracia; Domínguez Saldívar, Adriana (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2024)
Strategic Planning is an indispensable element for educational institutions to develop innovative projects and improve quality. This paper begins by presenting, in a succinct manner, the structure of the mexican educational system. Following some conceptual clarifications, it focuses on normal schools (higher education institutions), which through strategic planning can attract resources for their innovation, research, quality improvement, and infra structure projects, among others. Finally, the experience and achievements of a century-old normal school located in northeastern mexico are described.